Integration of solar panels with the architectural context of residential buildings, Erbil city as a case study - Abdulkadir, Binyad Maruf; Ibrahim, Polla Dilshad (Sulaimani Journal for Engineering Sciences, 2020)
In the last few decades, sustainable buildings and incorporating renewable energy become crucial to preserve life for current and next generations. Photovoltaics (PV) are widely used to produce energy for buildings which it can be seen worldwide and in Iraqi Kurdistan too. However, their integration into buildings, including residential buildings, become problematic for architectural quality of the buildings in general and residential buildings specifically as it is not integrated well and most of the times seem as it is not belong to it because they were not designed in congruence with the architectural form. Based on this, the researchers explored different innovative architectural integration approaches in developed world and innovative products that enable them to architecturally integrate it that can improve architectural quality besides generating solar energy in Iraqi Kurdistan. PV products have been divided for roofs and façades (with all it is parts) so that it can architecturally integrate better. An analysis for the rate and quality of used PV in Kurdistan has been done through set of criteria’s so that to specifically determine the problems, and through the analysis creating a residential (house) prototype and applying potential BIPV on it. Recommendations have been presented for how it can be architecturally integrated besides it is energy production .
Keywords: Photovoltaics; Residential Buildings; Architectural Integration of PV; BIPV; PV; Renewable Energy; Iraqi Kurdistan Region